An ANALYSIS OF SPEAKING PROBLEMS IN ONLINE ENGLISH PRESENTATION DURING COVID-19 PANDEMIC - Muhammad Yusuf (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2022)
Speaking is one way to convey information to others. Those speaking skills are the primary skills that need to be learned in English. To master English speaking skills, it is necessary to have sufficient habituation and practice to use English actively. A class presentation is one way to provide speaking training to students to become accustomed to using English in their daily lives. However, due to Covid-19, all learning activities are online through the platform, including the presentation class. This research investigates students' English language problems in online English presentations during the covid-19 pandemic. This research used qualitative phenomenological research, data taken from observations, questionnaires and semi-structured interviews obtained from eight participants. Data were analyzed using Nvivo 12 software to process data effectively and efficiently. The analysis results showed that the participants experienced linguistic problems (lack of grammar, pronunciation errors, and lack of vocabulary when speaking in online English presentations during the covid-19 pandemic. In addition, participants revealed that psychological problems (shyness, anxiety, and nervousness) made it difficult to speak English in online presentations. The findings also indicate that the causes of the problem were lack of practice, unsupportive environment, and mother tongue